(untitled) (Mustansiria Dental Journal, 2018)
Introduction: Temporomandibular joint internal derangements are progressive painful conditions that associated with limitation of mouth opening that caused by disruption within the internal aspects of the TMJ. The aim of this study was to evaluate the management of internal derangement of TMJ regarding pain intensity in temporomandibular joints and muscles of mastication and mouth opening. Materials and methods: This study was conducted in the Department of oral and maxillofacial surgery-college of dentistry Tikrit University. Twenty-one patients, 14 women and 7men with age range between 18-33 years old, were diagnosed with internal derangement of TMJ that were treated by intraarticular PRP. Results: show significant reduction of pain experienced by the patient after 12 weeks(P- < 0.0001). And show significant improvement of maximal interincisal mouth opening (P-<0.000).These finding demonstrating clearly that a significant improvement in both pain , mouth opening and clicking in the TMJ was achieved after the management. Conclusion: PRP injection to TMJ space for treatment of internal derangement are safe, effective, non-invasive method that help to reduce pain, joint noise and increase mouth opening, thus improving the jaw function.